The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1590/s1980-65742021006921
|View full text |Cite
|
Sign up to set email alerts
|

Relative age effect and age of peak performance: an analysis of women's football players in the Olympic games (1996-2016)

Abstract: The purpose of this study was to investigate the relative age effect and the age of peak performance of women's football players who participated in the Olympic Games from 1996 to 2016. Methods: Birth dates, playing positions, and nationality of all players registered in women's football competition in the Olympic Games (1996 to 2016) were collected. All data used in this study were obtained from the official website of the Federation Internationale de Football Association (www.fifa.com). The sample size of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…In particular, for the Under 17 and 20 age groups, a RAE was observed (i.e., Q1~33% vs. Q4~20%), especially when considering midfielders (i.e., Q1~37% vs Q4~17%) [ 20 ]. Differently, Andrew et al [ 21 ] found no RAE in UEFA European tournaments of U17, U19, and senior age groups between 2019–2022, whilst Barreira et al [ 28 ] reported no RAE in Olympic tournaments between 1996–2016. On the other hand, the few analyses on the national academy talent system (i.e., Swiss and U.S.) showed that the RAE is dependent by competition levels [ 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, for the Under 17 and 20 age groups, a RAE was observed (i.e., Q1~33% vs. Q4~20%), especially when considering midfielders (i.e., Q1~37% vs Q4~17%) [ 20 ]. Differently, Andrew et al [ 21 ] found no RAE in UEFA European tournaments of U17, U19, and senior age groups between 2019–2022, whilst Barreira et al [ 28 ] reported no RAE in Olympic tournaments between 1996–2016. On the other hand, the few analyses on the national academy talent system (i.e., Swiss and U.S.) showed that the RAE is dependent by competition levels [ 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, the finding indicates that relatively early-born players are over-represented among youth team players in the big clubs, as well as among senior teams in the big leagues. Among female international players, a quite recent study reported small, insignificant effects in Olympic tournaments since 1996 [ 63 ]. Sedano et al [ 57 ] had previously reported a clear effect among Spanish national teams; however, their sample was combined from U17, U19, U21, and senior players, with a rather small total N of 232.…”
Section: Introductionmentioning
confidence: 99%
“…Next, we calculated the coefficient of variation (CV) and mean age for each player before dividing the players into three groups: pre-peak age (<23 years old), peak age (23–27 years old), and post-peak age (>27 years old) ( Table 1 ). Given that peak age studies in women’s football are almost non-existent we based the peak age dichotomization on 1) the study by Barreira et al (2021) reporting a peak age of approximately 25 years old, and 2) studies on male elite players showing peak age band between 25–27 years old ( Dendir, 2016 ). We also felt extending this age band to include ages 23–25 years was appropriate due to the league being comparatively young in comparison to the men’s league.…”
Section: Methodsmentioning
confidence: 99%